THE EFFECT OF OIL PALM FIBERS AS REINFORCEMENT ON TRIBOLOGICAL PERFORMANCE OF POLYESTER COMPOSITE - YOUSIF, B. F.; EL-TAYEB, N. S. M. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2007)
In the present work, the effect of oil palm fibers on tribological performance of polyester composite against a polished stainless steel counterface is investigated using a pin-on-disc machine. Wear and friction characteristics of oil palm fiber reinforced polyester (OPRP) composite and neat polyester were tested at different sliding distances (0-5 km), sliding velocities (1.7-3.9m/s), and applied loads (30-70 N) under dry contact condition. SEM observations were performed on the worn surfaces to examine the damage features. The results showed that the test parameters significantly influenced the tribo-performance of OPRP composite and neat polyester. The presence of oil palm fiber in the polyester enhanced the wear property by about three to four times compared to neat polyester. In addition, the friction coefficient of OPRP composite was less by about 23% than that of the neat polyester. Wear mechanisms of OPRP composite were categorized by debonding, bending and tear of fibers, and high deformation in resinous region.